2014
DOI: 10.5312/wjo.v5.i4.486
|View full text |Cite
|
Sign up to set email alerts
|

Bone three-dimensional microstructural features of the common osteoporotic fracture sites

Abstract: Osteoporosis is a common metabolic skeletal disorder characterized by decreased bone mass and deteriorated bone structure, leading to increased susceptibility to fractures. With aging population, osteoporotic fractures are of global health and socioeconomic importance. The three-dimensional microstructural information of the common osteoporosis-related fracture sites, including vertebra, femoral neck and distal radius, is a key for fully understanding osteoporosis pathogenesis and predicting the fracture risk.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 67 publications
0
23
1
Order By: Relevance
“…Since the earliest changes of bone loss occur in the radius, it may be a more sensitive indicator of risk for asymptomatic fractures . Also, the lower end of the radius is composed predominantly of cancellous bone, and hence may be reflective of similar changes in the cancellous bones of the vertebrae . Some studies in lupus have also shown poor correlation of BMD with fracture incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Since the earliest changes of bone loss occur in the radius, it may be a more sensitive indicator of risk for asymptomatic fractures . Also, the lower end of the radius is composed predominantly of cancellous bone, and hence may be reflective of similar changes in the cancellous bones of the vertebrae . Some studies in lupus have also shown poor correlation of BMD with fracture incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Diminished OB activity associated with aging contributes to thinner and fewer trabeculae resulting in a loss of trabecular microarchitecture [42]. The consequent failure of the trabecular reinforcement of the inner cortical bone surface triggers cortical bone porosity, ultimately increasing the risk of fragility factures such as those involving the distal radius, distal tibia and proximal femur [42, 43]. Bone anabolic activity stimulated in older mice by the acute inhibition of CaMKK2 significantly improves trabecular microarchitecture while enhancing cortical bone geometry.…”
Section: Discussionmentioning
confidence: 99%
“…GC was proved to inhibit osteoblastic function, causing bone loss [26]. Several lines of evidence indicate the sympathetic nervous system in central regulation of bone remodeling [17,18,43]. Chronic stress is associated with pronounced and an enduring central and peripheral hyper-noradrenergic state [44].…”
Section: Possible Mechanisms For Bone Fragility Induced By Chronic Psmentioning
confidence: 99%
“…As the proportion of elderly persons has increased substantially and will continue to do so, osteoporotic fracture is a serious global health problem. Osteoporotic fractures might affect body movement, inducing disability, limiting daily activities and affecting the quality of life [2,17].…”
Section: Bone Homeostasis Regulated By the Central Nervous Systemmentioning
confidence: 99%